As geometrias do curso superior e os conteúdos geométricos do ensino médio : um estudo das relações existentes no entendimento de egressos da licenciatura em matemática do IFAL - Vieira, José Erisvaldo Lessa (2017)
This dissertation presents the results of a research that had as general objective to investigate the existing relations, in the understanding of the graduates of the degree in mathematics of the Federal Institute of Alagoas - IFAL, between the disciplines of geometry addressed in the teacher training and the geometric contents of high school level. This is a case of study research, that investigates 6 graduates in mathematics from IFAL, campus / Maceió, who work in the public school system. The data analysis, of a qualitative nature, was used of different techniques for the collection: documentary analysis, questionnaires and interviews. The theoretical contribution was focused on the theme of teacher training, teaching knowledge and geometry teaching. For a Teacher Training - Tardif (2014) and Imbernón (2011), mainly; Training of mathematics teacher was mainly based on Moreira and David (2014), Nacarato and Paiva (2008), Cury (2001); and in the teaching of geometry, studies Lorenzato (1995), Pavanello (2002) among others. From the documentary analysis and the subjects' speeches, it was possible to identify the content approach in the formation of the graduates through the theorems, axioms and demonstrations, according to the graduates favor a broad visualization of the contents of high school, before even entering the classroom. On the other hand, this approach is less used in their pedagogical practices, since the approach in textbooks begins intuitively, in addition to the students of basic education demonstrate a little bit of masterying while using i the arguments and / or demonstrations, hindering the gradual advance in geometric knowledge.